Impact of Social Media Marketing on Brand Awareness in Nepal - Bajracharya, Sajeet; Sah, Puja (Nepalese Journal of Business, 2024)
This study examines the impact of social media marketing on brand awareness in Nepal. Brand awareness is selected as a dependent variable. The selected independent variables are engagement rate, entertainment, interaction, trendiness, customization, e-WOM, and use of influencers. The study is based on primary data with 143 respondents. To achieve the purpose of the study, a structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of engagement rate, entertainment, interaction, trendiness, customization, e-WOM, and use of influencers on brand awareness in the context of Nepal. The results showed that engagement rate has a positive impact on brand awareness. It implies that increase in engagement rate leads to increase in the awareness of the brand. The result also revealed that entertainment has a positive impact on brand awareness. It implies increase in entertainment in social media marketing leads to increase in awareness of the brand. Moreover, interaction has a positive impact on brand awareness indicating that better interaction leads to increase in brand awareness. Furthermore, trendiness has a positive impact on brand awareness. It indicates that increase in trendiness leads to increase in brand awareness. Similarly, the result also showed that customization has a positive impact on brand awareness. It indicates that better customization leads to increase in brand awareness. Likewise, the result also showed that e-WOM has a positive impact on brand awareness. It indicates that increase in positive electronic word of mouth leads to increase in brand awareness. Further, the result also showed that use of influencers has a positive impact on brand awareness. It indicates that use of popular influencers leads to increase in awareness of the brand.